Peran Mediator Kepuasan Pelanggan dalam Menciptakan Sikap dan Perilaku Loyal - Dewanti, Retno; Tjandra, Hilman (Binus Business Review, 2014)
Condition of customers who are increasingly critical in terms of quality forces company to be able to maintain and improve the quality of its products in order to avoid claim or dissatisfaction from customers to the company to remain competitive with other similar companies. Handling customer complaints keeps customer to no change product. Satisfied customers are likely to behave and act loyal to the company. This study used questionnaire distributed to the customers of cooking oil product displaying the hotline service on the packaging. Respondents of the research were 100 persons. Research used path analysis to analyze data. Results shows that the quality of the product and handling customer complaint significantly affect customer satisfaction so as to create loyal attitude and behavior.